IMPROVING THE IMAGE OF THE GENERAL ELECTION COMMISSION (KPU) AFTER ISSUING A REGULATION PROHIBITING LEGISLATIVE CANDIDATES CONVICTED OF CORRUPTION FROM CONTESTING THE 2019 ELECTIONS - Diah Widyawati,; Ahmad Sihabudin,; Heri Budianto, (International Journal of Social Science, 2024)
This research focuses on when the General Election Commission (KPU) issued KPU Regulation (PKPU) Number 20/2018 on the Nomination of Members of the House of Representatives, Provincial House of Representatives, and Regency/City Regional House of Representatives. This PKPU is the “PKPU on Candidates of Former Corruption Convicts." This regulation is controversial, causing polemics and dividing the community between the pros and cons. Various accusations were directed at the KPU, even accusations conveyed by the closest colleague, the Election Supervisory Agency (Bawaslu), which requested that the KPU obey higher regulations and ended in the Adjudication of Election Process Disputes. The peak of public distrust was the Judicial Review in the Supreme Court. Researchers use the Image Repair Theory to analyze an organization's response when its positive image and reputation are threatened. This research uses a postpositivist paradigm. Based on the research paradigm, the type and nature of this research are descriptive and qualitative. Data was collected using observation, interview, documentation, and literature study techniques. The results of the study showed that of the five crisis communication strategies, KPU used typologies, namely denial (simple denial, shift blame), evade responsibility (provocation, good intentions), and reduce offensiveness (bolstering, minimization, differentiation, transcendence, attack accuser). Four (4) typologies that are not used are defeasibility, accident, compensation, and mortification